Pelatihan Pembuatan Sabun Transparan dan Legalitas Usaha dalam Program UMKM Level Up di Desa Lerep - Khollaqul Alim, Mohammad; Mega Sari, Astri; Fattahul Alim, Mohammad; Surya Maulana, Bagus; Ragili Yanti, Yulia; Marbun, Reniandi; Dzaki Munawar, Maulana (Jurnal Pusat Inovasi Masyarakat, 2024)
Lerep Village, located at the foot of Mount Ungaran, West Ungaran District, Semarang Regency, has transformed into a tourist village. One of the important pillars in supporting the progress of tourist villages is the growth of competitive MSMEs. MSME players in Lerep Village experience difficulties in developing product innovations and do not yet have business legality so that their marketing reach has not expanded and product sales levels tend to stagnate. The method of implementing innovation includes socialization, interviews, discussions, and mentoring with a descriptive analysis approach. The data sources used are primary data, namely MSME players in Lerep Village and GenBI administrators of Semarang State University, as well as secondary data in the form of relevant literature studies. The results of this service show that the training program on transparent soap making and business legality has enabled MSMEs in Lerep Village to develop varied product innovations and official licenses so that they can attract more tourists and expand their market share. This has an impact on increasing income and welfare for MSME players in Lerep Village. The Level Up MSME program experienced several obstacles in its implementation, such as the low participation rate of participants, the fact that many MSME players are not technologically literate, and the minimal participation of the younger generation in entrepreneurship. Program sustainability efforts are carried out through further assistance so that Lerep Village MSME products can be of higher quality and competitive with other products.